A nationwide comparative study between private and public university students’ soft skills - Abdul Karim, Abdul Malek; Abdullah, Nabilah; Abdul Rahman, Abdul Malek; Noah, Sidek M; Wan Jaafar, Wan Marzuki; Othman, Joharry; Borhan, Lihanna; Badushah, Jamaluddin; Said, Hamdan (Springer Netherlands, 2012)
The main function of Higher Educational Institutions (HEIs) is to produce skilled and knowledgeable workforce who are able to not only function with minimal guidance but also to contribute effectively to the hiring organizations. Many studies have indicated that most HEIs have somewhat similar course content and thrived at producing students with good academic achievement. But what differentiated them from one another is their ability to develop knowledge workers with the right employability skills or ‘soft skills’ such as communication, problemsolving, interpersonal and other skills deemed important as the foundations by which they require to function at work regardless of the nature of employment. This paper reports findings of a large-scale study looking into the soft skills attainment of Malaysian HEI graduates. A quantitative survey design was employed whereby data were obtained through the administration of an instrument called the Malaysian Soft Skills Scale (My3S). My3S consists of 180 items covering seven elements namely Communications, Critical Thinking and Problem Solving, Teamwork, Moral and Professional Ethics, Leadership, Life Long Learning and Entrepreneurial aspects. The mean scores for the seven My3S subscales were found to be between 6.3 and 7.8 from the maximum possible score of 10. Specifically, comparisons were made between graduates of public and private institutions with respect to the seven elements. Findings of the study suggest that, in general, students of public HEIs scored higher in all seven skills. With respect to gender, male students scored higher than female students in all elements except for teamwork skills and moral and professional ethics. A comparison between fields of study showed that for both types of HEIs, technical students scored the highest in all skills except for moral and professional ethics. Based on the findings of this study, it is suggested that in addition to offering specific courses to improve soft skills attainment, HEIs need to embed soft skills in their academic curricula.